SINERGI LINTAS BUDAYA DALAM PEMBERDAYAAN PENDIDIKAN ISLAM DI MUSLIMEEN SCHOOL SONGKHLA THAILAND - Ahmad Ma'ruf; Hambali; Muhamatsakree Manyunu (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This community service activity focuses on cross-cultural synergy in empowering Islamic education at Muslimeen School, Songkhla, Thailand. The background to this activity is the need to strengthen the quality of Islamic education that is able to adapt to global dynamics while maintaining local values. Through a collaborative approach, the community service team provides teacher mentoring, learning methodology workshops, and educational technology-based training contextualized with Islamic culture and values. This activity also emphasizes cross-cultural dialogue between Indonesian and Thai educators to enrich pedagogical perspectives. The results of the community service demonstrate an increase in teacher capacity in designing active, inclusive, and relevant learning to meet student needs. In addition, this activity strengthens academic networks among Islamic educational institutions in the ASEAN region. Cross-cultural synergy has proven to be an effective strategy in optimizing the quality of Islamic education that is competitive and rooted in local wisdom.